EFEKTIFITAS PEMASANGAN ABSORBER TERHADAP KALIBRASI MEDAN ELEKTROMAGNET OPEN STRIPLINE - Priyo Wibowo (Widyariset, 2009)
The effectiveness of 4cm x 4cm x 4cm pyramidal absorber lining arrangement on stripline field strength calibration has been studied in the EN 55020 laboratory at Testing Technology Division, P2SMTP-LIPI. The calibration procedure refers to CISPR 20 using Toyo IM5/A software at 84 frequencies from 0.15 -150 MHz. The number of calibrations is the representation of absorber combination number. This is needed to get the value of. RF voltage stripline average deviations depending on absorber number. The result of the data analysis shows that the maximum decreasing of average deviation voltage is 11.186%. However such installation still gives average deviation 0.689dB above deviation limit of ± 2dB.